2019
DOI: 10.1002/pld3.127
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll catabolism precedes changes in chloroplast structure and proteome during leaf senescence

Abstract: The earliest visual changes of leaf senescence occur in the chloroplast as chlorophyll is degraded and photosynthesis declines. Yet, a comprehensive understanding of the sequence of catabolic events occurring in chloroplasts during natural leaf senescence is still missing. Here, we combined confocal and electron microscopy together with proteomics and biochemistry to follow structural and molecular changes during Arabidopsis leaf senescence. We observed that initiation of chlorophyll catabolism precedes other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 84 publications
1
49
0
Order By: Relevance
“…The onset of developmental leaf senescence is highly responsive to internal and external cues and is tightly regulated on the levels of transcriptome (Breeze et al, 2011;Woo et al, 2016), proteome (Tamary et al, 2019) and metabolome (Watanabe et al, 2013;Chrobok et al, 2016;Jafari et al, 2017). By characterization of aging pp2a-b9g leaves, we demonstrate the regulatory role of PP2A-B9g in SA signaling extends to the SA component of developmental leaf senescence under short-day conditions (Figs.…”
Section: Pp2a-b9g Regulates Sa Signaling In Both Plant Immunity and Dmentioning
confidence: 78%
“…The onset of developmental leaf senescence is highly responsive to internal and external cues and is tightly regulated on the levels of transcriptome (Breeze et al, 2011;Woo et al, 2016), proteome (Tamary et al, 2019) and metabolome (Watanabe et al, 2013;Chrobok et al, 2016;Jafari et al, 2017). By characterization of aging pp2a-b9g leaves, we demonstrate the regulatory role of PP2A-B9g in SA signaling extends to the SA component of developmental leaf senescence under short-day conditions (Figs.…”
Section: Pp2a-b9g Regulates Sa Signaling In Both Plant Immunity and Dmentioning
confidence: 78%
“…Overall, our results showed that the chosen leaf ranks had a gradually advanced source status, i.e., a gradual increase in their nitrogen remobilization processes. Moreover, since the strong activation of chlorophyll degradation in old leaves is always associated with a decrease in chloroplast volume and chloroplast size [49], our result suggested that L3 leaves were at the onset of senescence.…”
Section: S-methyl-l-cysteine Sulphoxide (Smcso) Gln Pro Asn Val Amentioning
confidence: 59%
“…Metabolites 2020, 10, x 4 of 16 gradual increase in their nitrogen remobilization processes. Moreover, since the strong activation of chlorophyll degradation in old leaves is always associated with a decrease in chloroplast volume and chloroplast size [49], our result suggested that L3 leaves were at the onset of senescence. Next, we quantified amino acid contents in the different leaf ranks (complete dataset available in Supplementary Table S1).…”
Section: S-methyl-l-cysteine Sulphoxide (Smcso) Gln Pro Asn Val Amentioning
confidence: 59%
“…The photosynthetic capacity of the leaf suddenly drops due to the loss of chlorophyll during senescence. The production of carbohydrates, amino acids and other molecules is displaced by the degradation of macromolecules such as protein, lipids and nucleic acids (DNA and RNA), and the released nutrients are mobilised to plant parts such as new buds, young leaves, developing fruits and seeds or to storage organs for the future growing season (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of leaf senescence is affected by various factors including age, abiotic and biotic stress, and plant hormones (36,37). Effects of plant hormones on senescence such as auxin, cytokinin, gibberellin, ethylene ABA, SA and JA are well-known (29,35,36). Moreover, the effect of KAR1 on leaf senescence is still lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%